(untitled) (Research, Society and Development, 2021)
Meat products have high percentages of fat, especially saturated. Studies show the feasibility of replacing fat with other types of ingredients in order to improve the nutritional content. Passion fruit albedo is seen as a potential fat substitute, as it has a high level of fiber, protein, and minerals. Furthermore, it is rich in pectin, a polysaccharide formed by galacturonic acid. The present study aimed to identify, in the scientific literature, the functional relevance of the passion fruit albedo flour in the enrichment of meat products. The research is a Narrative Review, based on publications in the following scientific databases: CAPES, Pubmed, ScienceDirect, and Academic Google. The research consisted of the use of the following descriptors and operators: “sausage” OR “meat products” AND “passion fruit albedo” in English, in the years 2012 to 2021. The consumption of passion fruit albedo flour is associated with several health benefits, such as delayed gastric emptying and intestinal transit, increased feeling of satiety, decreased levels of glucose, and total blood cholesterol. The incorporation of passion fruit albedo flour in the percentage of 2.5% can cause changes in the physicochemical and technological characteristics of meat products. Therefore, its use contributes to formulations with high nutritional value in the product, reduces environmental impacts, and adds value to solid parts of passion fruit. However, more studies are needed in the area of food product development and more characterizations about the benefits of this enrichment and biochemical interactions with the food matrix, for further commercialization.